Optimal Reduction of Technical Power Losses in Radial Distribution Networks Using Differential Evolution for Distributed Generation: A Case Study of the Azare Substation in Nigeria - Muhammad B. MUHAMMAD; Muhammad Y. ABDULLAHI; Aminu BALA (FUDMA Journal of Engineering and Technology, 2026)
Technical power losses in distribution networks considerably affect the efficiency, reliability, and economic performance of power utilities, especially in developing nations. This study introduces an optimized method to reduce technical power losses in a radial distribution system by optimally placing Distributed Generation (DG). A Differential Evolution (DE) algorithm is used to find the best locations and sizes of DG units in a 9-bus test system representing the Azare distribution substation in Nigeria. Load flow analysis is performed in MATLAB using the Newton–Raphson method within an optimization framework for precise fitness evaluation. At the same time, the optimized DG settings are validated in PowerWorld Simulator to confirm practical relevance and provide system visualization. Results reveal that placing DG units at buses 5 and 9 decreases total system power loss from 0.2927 MW to 0.0352 MW, significantly improving efficiency. Voltage profiles are also enhanced, with all buses maintaining acceptable levels between 0.95 and 1.05 pu. The study demonstrates that combining metaheuristic optimization with power system simulation tools offers a practical solution for reducing technical losses in distribution networks, and the proposed approach provides a scalable framework for enhancing power system performance in similar developing contexts.